Photocatalytic Decolorization of Acid Red 4 Azo Dye by Using Immobilized TiO2 Microparticle and Nanoparticle Catalysts - Sugiyana, Doni; Soenoko, Bambang; Handajani, Marisa; Suprihanto, Suprihanto (UI Scholars Hub, 2012)
This research studied the synthesis of immobilized TiO2 microparticle and nanoparticle catalyst materials and evaluated its photocatalytic activity on the decolorization of Acid Red 4 (AR4) azo dye solution. TiO2 microparticles were immobilized on an acrylic plate, while TiO2 nanoparticles were immobilised on a glass plate. TiO2 nanoparticles were embedded in a nanofiber support layer to enhance photocatalytic performance, forming a nanofiber-nanoparticle composite on the glass plate. In the catalyst load 2.0 g/l, the performance of the photocatalytic layer of immobilized catalyst (k '= 0.013/min) was better than that of the suspended catalyst (k' = 0.008/min). Photocatalytic decolorization efficiency of TiO2 immobilized catalysts of nanoparticle sized reached 82.3% in irradiation time of 2 hours, which was higher than microparticle sized catalysts (77.8%). The technique of TiO2 nanofiber–nanoparticle composite showed improved photocatalytic kinetics (k’= 0.018/min) compared to a single layer of nanoparticle catalyst (k'= 0.015/min). Immobilized TiO2 catalysts remain effective with repeated use despite a slight decrease in processing efficiency.